Aplicabilidad del derecho a la seguridad social como derecho fundamental de las personas de la tercera edad frente a la pensión familiar (2015)
This research seeks to make a detailed analysis of the law 1580, 2012, deepening its scope and applicability in terms of the benefits it is incorporated into social security as a fundamental right for people seniors, said analysis also seeks to identify those elements that might make more effective this rule, gaps and limitations in turn a detailed jurisprudential analysis is performed on family pension. 6 This dissertation analyzed retrospectively the evolution undergone by the pension system, which are basis for the creation of law 1580 2012. Finally a comparative analysis of family pension with other laws worldwide is performed, since Colombia is not the pioneer in this pension figure, and Peru had included this figure in its pension system